Microbiological characterization of fresh bee pollens from the Aegean region of Turkey - Altintas, Levent; Sevin, Sedat; Kahraman, Hatice Ahu; Tutun, Hidayet; Sababoglu, Ezgi; Keyvan, Erhan (Journal of the Hellenic Veterinary Medical Society, 2022)
ABSTRACT. The aim of this study is to characterize the microbiological safety of Turkish fresh bee pollen for the first time. Twenty-one fresh bee pollen samples were purchased from local beekeepers between September 2020 and October 2020 in Muğla, İzmir, Kütahya and Afyon provinces in the Aegean region of Turkey. The samples were analyzed for total aerobic bacteria, total coliform bacteria, total psychotropic microorganism, total lactic acid bacteria, Staphyloccus aureus, sulfite-reducing clostridia spores, yeast and mold. Total ochratoxin and aflatoxin levels were measured using lateral flow kit in samples contaminated with mycotoxigenic molds. The counts of the microorganisms ranged from 3.70 to 5.42 log CFU g-1 for the aerobic mesophilic, 3.0 to 5.40 log CFU g -1 for psychrotrophs, 3.85 to 5.78 log CFU g -1 for lactic acid bacteria (LAB), 3.0 to 5.45 log CFU g-1 for yeasts-molds, and <10 to 5.0 log CFU g-1 for total coliforms in the samples. Besides, S. aureus and sulfite reducing clostridia were not detected among the samples. The predominant mold genera in samples were Aspergillus sp. Penicillium sp. and Alternaria sp. Five samples contaminated with mycotoxicogenic molds had aflatoxins in the range of 2.96-9.71 µg/kg. According to the study results, comprehensive prevention, control and surveillance strategies need to be established to reduce bacteria and mycotoxin contaminations in fresh bee pollen. Legal regulation of bee pollen as food supplement and legal limit of mycotoxins in bee pollen should be defined.